Effect of single- and double-row rotator cuff repair at the tendon-to-bone interface: preliminary results using an in vivo sheep model - Baums, M. H.; Schminke, B.; Posmyk, A.; Miosge, N.; Klinger, H.-M.; Lakemeier, S. (Archives of orthopaedic and trauma surgery, 2015)
Introduction The clinical superiority of the double-row technique is still a subject of controversial debate in rotator cuff repair. We hypothesised that the expression of different collagen types will differ between double-row and single-row rotator cuff repair indicating a faster healing response by the double-row technique. Materials and methods Twenty-four mature female sheep were randomly assembled to two different groups in which a surgically created acute infraspinatus tendon tear was fixed using either a modified single- or double-row repair technique. Shoulder joints from female sheep cadavers of identical age, bone maturity, and weight served as untreated control cluster. Expression of type I, II, and III collagen was observed in the tendon-to-bone junction along with recovering changes in the fibrocartilage zone after immunohistological tissue staining at 1, 2, 3, 6, 12, and 26 weeks postoperatively. Results Expression of type III collagen remained positive until 6 weeks after surgery in the double-row group, whereas it was detectable for 12 weeks in the single-row group. In both groups, type I collagen expression increased after 12 weeks. Type II collagen expression was increased after 12 weeks in the double-row versus single-row group. Clusters of chondrocytes were only visible between week 6 and 12 in the double-row group. Conclusions The study demonstrates differences regarding the expression of type I and type III collagen in the tendon-to-bone junction following double-row rotator cuff repair compared to single-row repair. The healing response in this acute repair model is faster in the double-row group during the investigated healing period.